How Social Relationships Affect Writers - Karen A. Keller (Networks: An Online Journal for Teacher Research, 2004)
My students always enjoyed working in groups. They begged to be with their friends whenever I assigned a group project. In general, I dreaded allowing students to work in groups. I feared the classroom disruption from students who could not stay on task. And I wondered if students would do their best work in a group. Yet, I had to admit that as a graduate student, I found that some of my best work resulted from work in a group setting.